A corpus-based study of elderly and young speakers of European Portuguese: Acoustic correlates and their impact on speech recognition performance - Pellegrini, T.; Hämäläinen, A.; De Mareüil, P. B.; Tjalve, M.; Trancoso, I.; Candeias, S.; Dias, M. S.; Braga, D. (Proceedings of the 14th Annual Conference of the International Speech Communication Association (INTERSPEECH 2013), 2013)
This paper presents a study of European Portuguese elderly speech, in which the acoustic characteristics of two groups of elderly speakers (aged 60-75 and over 75) are compared with those of young adult speakers (aged 19-30). The correlation between age and a set of 14 acoustic features was investigated, and decision trees were used to establish the relative importance of the features. A greater use of pauses characterized speakers aged 60 and over. For female speakers, speech rate also appeared to correlate with age. For male speakers, jitter distinguished between speakers aged 60-75 and older. The correlation between the features and speech recognition performance was also investigated. Word error rate correlated mostly with the use of pauses, speech rate, and the ratio of long phone realizations. Finally, by comparing the phone sequences used by the recognizer on the most frequent words, we observed that the young adult speakers reduced schwas more than the elderly speakers. This result seems to confirm the common idea that young speakers reduce articulation more than older speakers. Further investigation is needed to confirm this result by determining whether this is due to ageing or to the generation gap.